Relationship between Age, Gender, Education Level, Employment Status and Comorbidity with Nutritional Status in Hemodialysis Patients - Zuraida, Reni; Yoga, M. Agung Prasetya Adnyana; Angraini, Dian Isti; Sayekti, Wuryaningsih Dwi; Berawi, Khairun Nisa (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This research aimed to determine the relationship between age, gender, education level, employment status, and comorbidities with nutritional status in hemodialysis patients. It employed a cross-sectional design. The population consisted of end-stage renal disease outpatients undergoing hemodialysis, totaling 84 respondents aged 19‒59 years. The sampling method utilized was simple random sampling. This research was conducted from October to November 2024. Nutritional status was measured using the Subjective Global Assessment (SGA) questionnaire. Statistical tests employed included chi-square and logistic regression analyses. The statistical results indicated a significant relationship between employment status and nutritional status, comorbidity and nutritional status in hemodialysis patients (p<0.05). No significant relationships were found between age, gender, and education level with nutritional status among hemodialysis patients (p>0.05). The factors associated with nutritional status among hemodialysis patients are comorbidity (OR=6.618; 95% CI:2.124–20.619, p<0.05) and employment status (OR=5.887; 95% CI:1.585–21.870, p<0.05). Malnutrition is closely related to the presence of comorbidities in hemodialysis patients; therefore, it is crucial to treat and manage comorbidities to prevent the progression of malnutrition in this population. Health workers in the hemodialysis department should pay more attention to the nutritional status of patients who are unemployed.